397 TESTING THE DIVERGENT PATHWAY MODEL FOR MELANOMA IN A LARGE US POPULATION-BASED CASE COMPARISON STUDY. Issue 1 (1st January 2007) - Kunkel, D.; Tandberg, D.; Berwick, M.
Abstract : Purpose of Study: Post hoc analysis of a large US population-based study of melanoma was carried out to test Whiteman's divergent pathway model that suggests different etiologic pathways for melanoma based on (1) pattern of sun exposure, as characterized by anatomic site, and (2) host factors, such as propensity for melanocyte proliferation, as characterized by nevus status. Methods: Study subjects consisted of 528 newly diagnosed cases of melanoma among Caucasian residents of Connecticut. Nurse-interviewers obtained information on age, gender, hair color, eye color, skin color, history of sun exposure, history of painful sunburns, anatomic site of melanoma, and number of nevi on both arms and the back. The variable 'nevus prone' was generated and scored as true if the number of nevi was greater than five. A logistic model was fitted and age-adjusted simultaneous odds ratios with 95% confidence intervals were generated using nevus-prone as the dependent variable. Summary of Results: See the table below for summary statistics. Conclusions: The study found a statistically significant relationship ( p < .01) between anatomic site of melanoma and nevus-prone status. This is consistent with the prediction of the divergent pathway model for different paths to melanoma formation based on pattern of sun exposure and host propensity for melanocyte proliferation. Further investigation into the biologic basis for the divergent pathway is warranted so that skin cancer prevention strategies can be tailored to specific populations.